Continuous light increases growth, daily carbon gain, antioxidants, and alters carbohydrate metabolism in a cultivated and a wild tomato species - Haque, Mohammad S.; Kjaer, Katrine H.; Rosenqvist, Eva; Ottosen, Carl-Otto (Frontiers in Plant Science, 2015)
Cultivated tomato species develop leaf injury while grown in continuous light (CL). Growth, photosynthesis, carbohydrate metabolism and antioxidative enzyme activities of a cultivated (Solanum lycopersicum L. ‘Aromata’) and a wild tomato species (Solanum pimpinellifolium L.) were compared in this study aiming to analyse the species-specific differences and thermoperiod effects in responses to CL. The species were subjected to three photoperiodic treatments for 12 days in climate chambers: 16-h photoperiod with a light/dark temperature of 26/16ºC (P16D10 or control); CL with a constant temperature of 23ºC (P24D0); CL with a variable temperature of 26/16ºC (P24D10). The results showed that both species grown in CL had higher dry matter production due to the continuous photosynthesis and a subsequent increase in carbon gain. In S. lycopersicum, the rate of photosynthesis and the maximum photochemical efficiency of photosystem II declined in CL with the development of leaf chlorosis, reduction in the leaf chlorophyll content and a higher activity of antioxidative enzymes. The normal diurnal patterns of starch and sugar were only present under control conditions. The results demonstrated that CL conditions mainly affected the photosynthetic apparatus of a cultivated species (S. lycopersicum), and to a less degree to the wild species (S. pimpinellifolium). The negative effects of the CL could be alleviated by diurnal temperature variations, but the physiological mechanisms behind these are less clear. The results also show that the genetic potential for reducing the negative effects of CL does exist in the tomato germplasm.